Measuring the duration of formative phases for energy technologies - Bento, N.; Wilson, C. (Environmental Innovation and Societal Transitions, 2016)
Innovation processes during the early period of a technology’s development establish the conditions for widespread commercialization. For comparative analysis of innovation processes across technologies, a common operational definition of the formative phase is needed. This paper develops a set of indicators to measure the start and end points of formative phases with reference to key innovation processes including experimentation and market formation. The indicators are then applied to measure the formative phase durations of sixteen energy technologies covering a range of historical periods and applications. Formative phases are found to last 22 years on average. Determinants of formative phase duration are explored. Duration does not appear to be explained by unit scale, up-scaling, nor initial cost. However, technologies that are ready substitutes for incumbents have shorter formative phases, ceteris paribus. Policy implications include the potentials and risks of accelerating formative phases to push low carbon technologies into the market.